Effect of thiamethoxam seed treatment in peanut. Issue 2 (8th November 2021) - Monfort, Scott; Culbreath, Albert; Abney, Mark; Brandenburg, Rick; Royals, Brian; Jordan, David; Herbert, Ames; Taylor, Sally; Malone, Sean
Abstract: Tobacco thrips ( Frankliniella fusca ) and tomato spotted wilt (TSW) orthotospovirus (family Tospoviridae, genus Orthotospovirus) can reduce peanut ( Arachis hypogaea L.) yield. Systemic insecticides are applied in the seed furrow at planting and to peanut foliage to reduce injury from tobacco thrips and decrease incidence of TSW. Research was conducted in Georgia, North Carolina, South Carolina, and Virginia in 2013 and 2014 to compare the effect of the following treatments on tobacco thrips feeding injury and expression of TSW in peanut: thiamethoxam seed treatment, thiamethoxam seed treatment followed by acephate 3 weeks after planting, phorate applied in the seed furrow at planting, and a nontreated check. Tobacco thrips feeding injury and TSW incidence were significantly higher in thiamethoxam and thiamethoxam followed by acephate‐treated peanut than peanut treated with phorate. Thiamethoxan seed treatment followed by acephate resulted in significantly lower tobacco thrips feeding injury compared to thiamethoxam seed treatment alone. Yield of Virginia market type cultivars was greater when thiamethoxam was followed by acephate applied to peanut foliage or when phorate was applied compared with nontreated peanut or the seed treatment alone. Runner market type cultivars yielded higher when phorate was applied compared with nontreated peanut while peanut treated with thiamethoxam with or with acephate yielded similar to both of these treatments. Core Ideas: Thiamethoxam was less effective than phorate in preventing visible injury caused by thrips. Protection of yield from thrips injury by insecticides was important for both market types. Less tomato spotted wilt was observed when phorate was applied compared with thiamethoxam.